2014
DOI: 10.3357/asem.4000.2014
|View full text |Cite
|
Sign up to set email alerts
|

Aircraft-Assisted Pilot Suicides: Lessons to be Learned

Abstract: Aircraft assisted suicides were studied in the United States, United Kingdom, Germany, and Finland during 1956-2012 by means of literature search and accident case analysis. According to our study the frequency varied slightly between the studies. Overall, the new estimate of aircraft assisted suicides in the United States in a 20-yr period (1993-2012) is 0.33% (95% CI 0.21-0.49) (24/7244). In the detailed accident case analysis, it was found that in five out of the eight cases from the United States, someone … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
16
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 0 publications
0
16
0
1
Order By: Relevance
“…Figure 1 represents the studies identified at each phase of our search using the PRISMA flow diagram. The search strategy identified 709 papers of which 20 met the inclusion criteria ( 8 27 ). We divided the studies into three groups, displayed accordingly: depression and associated psychosocial factors (Table 1 ), suicide and substance abuse (Table 2 ), and sleep and fatigue (Table 3 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Figure 1 represents the studies identified at each phase of our search using the PRISMA flow diagram. The search strategy identified 709 papers of which 20 met the inclusion criteria ( 8 27 ). We divided the studies into three groups, displayed accordingly: depression and associated psychosocial factors (Table 1 ), suicide and substance abuse (Table 2 ), and sleep and fatigue (Table 3 ).…”
Section: Resultsmentioning
confidence: 99%
“…However, suicidal ideation does not necessarily lead to a suicide attempt. Regarding fatal aircraft accidents, between 1993 and 2012 U.S. aircraft-assisted suicide by pilots totals 0.33% (24/7,244 fatal accidents) ( 18 , 27 ).…”
Section: Resultsmentioning
confidence: 99%
“…Vuorio et al. () stated that aircraft‐assisted suicides in the United States were about 0.33% of all general aviation accidents. Bor, Field, and Scragg () estimated a slightly higher rate at between 0.72% and 2.4%, and Schwark et al.…”
mentioning
confidence: 99%
“…Curtailing suicide, whether aircraft assisted or not, is difficult. Estimates are that between one‐third to one‐half (Martin et al., ; Owen et al., ) of completed suicides directly communicated their intention beforehand, with 18% to 22% letting family physicians or mental health professionals know (Martin et al., ; Vuorio et al., ), and 60% letting spouses or significant others know (Martin et al., ). Piloting is one of the few occupations that require frequent and rigorous health checks; however, pilots may fear questions about mental health may jeopardize careers, livelihood, and enjoyment of flying (Bor et al., ).…”
mentioning
confidence: 99%
“…The probability that aircrafts are used to assist suicide is exceedingly low. We have recently estimated that suicide accounts for about 0.3% of fatal accident cases in general aviation, which would be approximately 8 cases in the USA between 2003-2012 ( 1 ); but this figure is likely to be even lower in commercial air transport. However, in commercial air transport the consequences are severe, in that one accident can cause many deaths.…”
mentioning
confidence: 99%